Evaluation of the performance of a prior tacrolimus population pharmacokinetic kidney transplant model among adult allogeneic hematopoietic stem cell transplant patients. Issue 3 (27th January 2021) - Zhu, Jing; Campagne, Olivia; Torrice, Chad D.; Flynn, Gabrielle; Miller, Jordan A.; Patel, Tejendra; Suzuki, Oscar; Ptachcinski, Jonathan R.; Armistead, Paul M.; Wiltshire, Tim; Mager, Donald E.; Weiner, Daniel L.; et al.
Abstract : Abstract: Tacrolimus is a calcineurin inhibitor used to prevent acute graft versus host disease in adult patients receiving allogeneic hematopoietic stem cell transplantation (HCT). Previous population pharmacokinetic (PK) models have been developed in solid organ transplant, yet none exists for patients receiving HCT. The primary objectives of this study were to (1) use a previously published population PK model in adult patients who underwent kidney transplant and apply it to allogeneic HCT; (2) evaluate model‐predicted tacrolimus steady‐state trough concentrations and simulations in patients receiving HCT; and (3) evaluate covariates that affect tacrolimus PK in allogeneic HCT. A total of 252 adult patients receiving allogeneic HCT were included in the study. They received oral tacrolimus twice daily (0.03 mg/kg) starting 3 days prior to transplant. Data for these analyses included baseline clinical and demographic data, genotype data for single nucleotide polymorphisms in CYP3A4 / 5 and ABCB1, and the first tacrolimus steady‐state trough concentration. A dosing simulation strategy based on observed trough concentrations (rather than model‐based predictions) resulted in 12% more patients successfully achieving tacrolimus trough concentrations within the institutional target range (5–10 ng/ml). Stepwise covariate analyses identified HLA match and conditioning regimen (myeloablative vs. reduced intensity) as significant covariates. Ultimately, a previously published tacrolimus population PK model in kidney transplant provided a platform to help establish a model‐based dose adjustment strategy in patients receiving allogenic HCT, and identified HCT‐specific covariates to be considered for future prospective studies. Study Highlights WHAT IS THE CURRENT KNOWLEDGE ON THE TOPIC? Tacrolimus is a cornerstone immunosuppressant used in patients who undergo organ transplantations. However, because of its narrow therapeutic index and wide interpatient pharmacokinetic (PK) variability, optimizing its dose is crucial to maximize efficacy and minimize tacrolimus‐induced toxicities. Prior to this study, no tacrolimus population PK models have been developed for adult patients receiving allogeneic hematopoietic stem cell transplantation (HCT). Therefore, research effort was warranted to develop a population PK model that begins to propose more precision tacrolimus dosing and begins to address both a clinical and scientific gap in this patient population. WHAT QUESTION DID THIS STUDY ADDRESS? The study addressed whether there is value in utilizing the observed tacrolimus steady‐state trough concentrations from patients receiving allogeneic HCT within the context of a pre‐existing population PK model developed for kidney transplant. The study also addressed whether there are clinically relevant covariates specific to adult patients receiving allogeneic HCT. WHAT DOES THIS STUDY ADD TO OUR KNOWLEDGE? Inclusion of a single steady‐state tacrolimus trough concentration is beneficial to model predictions. The dosing simulation strategy based on observed tacrolimus concentration, rather than the model‐predicted concentration, resulted in more patients achieving the target range at first steady‐state collection. Future studies should evaluate HLA matching and myeloablative conditioning versus reduced intensity conditioning regimens as covariates. These data and model‐informed dose adjustments should be included in future prospective studies. This research could also serve as a template as to how to assess the utility of prior information for other disease settings. HOW MIGHT THIS CHANGE CLINICAL PHARMACOLOGY OR TRANSLATIONAL SCIENCE? The M2 model fitting method and D2 dosing simulation method can be applied to other clinical pharmacology studies where only a single steady‐state trough concentration is available per patient in the presence of a previously published population PK model.